ECG evaluation in 11 949 Italian teenagers: results of screening in secondary school. Issue 2 (February 2022) - Mancone, Massimo; Maestrini, Viviana; Fusto, Antonio; Adamo, Francesco; Scarparo, Paola; D'Ambrosi, Alessandra; Cinque, Alessandra; Gatto, Maria Chiara; Salvi, Nicolò; Agnes, Gianluca; Pucci, Mariateresa; Birtolo, Lucia Ilaria; et al.
Abstract : Aim: There is lack of evidence regarding the screening role of ECG for sudden cardiac death (SCD) prevention. Our aim was to evaluate the prevalence of ECG abnormalities among teenagers according to sport participation and competitive status. Methods: Eleven thousand nine hundred and forty-nine Italian pupils from 179 secondary schools (13–19 years) were consecutively enrolled. ECG abnormalities were divided into minor and major. Medical history, clinical examination and sport activity information were acquired. Further evaluations were suggested in case of major ECG abnormalities. Follow-up was performed at 2 years. Results: N = 1945 (16%) pupils had ECG abnormalities. Major ECG abnormalities were detected in 13% of the cohort, minor in 34%. ECG abnormalities were more common in nonathletes compared with athletes. A diagnosis of cardiac disease was reached in 25 (1.6%) of the pupils with major ECG abnormalities. Conclusion: ECG abnormalities are common among young populations and more prevalent in nonathletes. Among pupils with major ECG abnormalities 1.6% had a cardiac disease diagnosis. Our results are in line with the data supporting ECG screening in the general young population.